Analisis Ketersediaan Sarana Pencegahan Dan Penanggulangan Kebakaran Sebagai Upaya Mengurangi Kerugian Akibat TerjadinyaKebakaran Di Pt Tyfountex Indonesia - Anugrah, Jaya, Tarwaka, PGDip., Sc., M.Erg, Sri Darnoto, SKM., MPH (2016)
One of the potential dangers that can occur in the workplace is the Fire. Fire hazards can occur at any time, anytime and anywhere as there are many opportunities that can lead to fires. This study aimed to analyze the availability of fire prevention and control in an effort to reduce losses due to fires. Type of research is qualitative descriptive research with a total sample of 30 samples were obtained by using purposive sampling. The result showed that there are 25 potential fire hazard with 8 hazards included in the high-risk level , two sources of danger included in the moderate risk level, and 15 sources of danger included in the low level of risk. Identification of means of fire prevention and suppression showed that on some means of fire prevention and control as well as the firefighting unit, the terms become squads and fire prevention coordinator has not been in accordance with the legal basis. Companies need to identify fire hazards, risk assessment and identification of means of fire prevention and control efforts to prevent and suppress fires in the workplace